Gene regulation by let-7 microRNAs during human and sheep placental development - Ali, Asghar, author; Winger, Quinton A., advisor; Bouma, Gerrit J., advisor; Chicco, Adam, committee member; Garrity, Deborah, committee member (Colorado State University. Libraries, 2020)
Intrauterine growth restriction (IUGR) is a major cause of perinatal morbidity and mortality and affects more than 30 million infants every year across the world. Its occurrence is 5–15% of all pregnancies in the United States and 10-55% in developing countries. Most common etiology of IUGR is impaired placental development. Structural and functional abnormalities in placenta can also lead to preeclampsia (PE), still birth and spontaneous abortion. Conditions like IUGR and PE are usually not detected until later stages of gestation. Hence, there is a need to better understand the placental development and function to improve diagnosis and treatment of placenta-associated disorders. In this study, we investigated genetic pathways regulated by let-7 miRNAs and their potential role in pathogenesis of malformed placenta. Let-7 miRNAs are markers of cell differentiation and reduce the expression of several genes by translational repression. Biogenesis of let-7 miRNAs is suppressed by LIN28 which is an RNA binding oncofetal protein with two paralogs, LIN28A and LIN28B. LIN28 is high and let-7 miRNAs are low in proliferating stem cells whereas LIN28 is low and let-7 miRNAs are high in differentiated cells. LIN28-let-7 axis determines fate of cells by regulating the expression of genes associated with cell proliferation and differentiation. In human placenta, LIN28 is mainly found in trophoblast cells and the fetal portion of placenta comprises mainly of trophoblast cells. We found that in term human placentas from IUGR pregnancies, LIN28 is low and let-7 miRNAs are high compared to placentas from control placentas. We further saw a reduction in the expression of AT-Rich Interaction Domain 3A (ARID3A) and AT-Rich Interaction Domain 3B (ARID3B). ARID3A and ARID3B promote cell proliferation by transcriptional regulation of stemness genes. In immortalized first trimester human trophoblast (ACH-3P) cells, ARID3A and ARID3B complex with lysine demethylase 4C (KDM4C) to make the ARID3B-complex. This complex binds the promoter regions of proliferation-associated genes such as high mobility group AT-hook 1 (HMGA1), transcriptional regulator Myc-like (c-MYC), vascular endothelial growth factor A (VEGF-A) and Wnt family member 1 (WNT1). These genes are also targeted by let-7 miRNAs. LIN28 knockout ACH-3P cells have significantly increased let-7 miRNAs and significantly reduced HMGA1, c-MYC, VEGF-A and WNT1. We also saw significant reduction in ARID3A and ARID3B in LIN28 knockout ACH-3P cells. ACH-3P cells with ARID3B knockout also showed significant reduction in HMGA1, c-MYC, VEGF-A and WNT1. Both LIN28 knockout and ARID3B knockout in ACH-3P cells resulted in reduced cell proliferation compared to control. These results suggest that proliferation-associated genes in trophoblast cells are regulated through LIN28-let-7-ARID3B pathway. Trophectoderm (TE) specific knockdown of LIN28 in sheep led to reduced conceptus elongation at day 16 of gestation. Furthermore, LIN28 knockdown day 16 TE had significantly increased let-7 miRNAs and significantly reduced expression of proliferation factors including insulin like growth factor 2 mRNA binding proteins (IGF2BPs), HMGA1, ARID3B and c-MYC. From these findings, we interpret that LIN28-let-7-ARID3B pathways regulates proliferation of trophoblast cells and is potentially associated with etiology of IUGR.
Keywords: conceptus; LIN28; trophoblast; growth restriction; ARID3B-complex; placenta